REVITALISASI PRANATA SOSIAL DAN REKONSTRUKSI PENYELENGGARAAN MUSRENBANG - Peribadi Peribadi; Megawati Asrul Tawulo (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2021)
The study aims to develop a strategic formulation by means of integrating and synthesizing traditional typical planning pattern called Meobu-Obu and Musrenbang (Community consultation on development planning held annually from village level to national level) as participatory development planning occurring so far in the area of South Konawe Regency Government. The attempts of reconstructing and functionalizing rural social institutions were developed through community studies, participatory studies and eclectic case studies. The results show that the process of utilizing Village Funds (VF) still focuses more on physical development aspect rather than the aspect of community socio-economic empowerment. Meanwhile, the process of organizing the Musrenbang tends to be formalistic to merely abort the procedural aspects. Similarly, the institution of kalosara still wrestles with ritualistic field of un sich continuosly, so that the sacralization of kalosara culture has not entered the developmental field yet. It is exactly in this context that the result of research offers a formulation of Musrenbang based on cultural value of kalosara to be used in the future in the attempt of building the rural areas, particularly in the mainland of Southeast Sulawesi Province.